Allozyme variation of the endemic and vulnerable Dyera lowii Hook.f. in Central Kalimantan: Implications for genetic resources conservation - Tri Suwarni Wahyudiningsih; Mohammad Naiem; Sapto Indrioko; Issirep Sumardi (Universitas Gadjah Mada, 2014)
Dyera lowii is an endemic and vulnerable tree species of commercial value as chewing gum found inpeat swamp forests, scatteredly distributed in Sumatra, Kalimantan, and Peninsular Malaysia. Their existenceis now under severe threat due to habitat conversion. This study is aimed to assess genetic diversity withinfour natural populations (Hampangen, Parahangan, Sebangau, Selat Nusa ) and one plantation in CentralKalimantan based on allozyme variation. Electrophoresis procedures were conducted with an isoelectricfocusing polyacrylamide slab gel system. The result showed high genetic diversity (HE=0.52) and gene fl ow(3.402) seemed to be effective. A total of 14 alleles were found among all the analysed population. Meannumber of alleles per locus (Aa) was 3.206, and the effective number of alleles per locus (Ae) was 2.21. Geneticdifferentiation between populations (FST) was signifi cant at the moderately level (0.0685). Most allozymevariation was found within population (93.2%). Special attention is essential to conserve a private allele ofGot-1-e (9%) at Selat Nusa population. Sebangau population missed the alleles of Est-2-b and Got-1-a, as foundin other populations. Selat Nusa population is expected to enhance the effective management for geneticresources conservation of this vulnerable species in the future.